Signature of surface periodicity in the electronic structure of Si(1 1 1)-(7 × 7). (20th April 2017) - Sheverdyaeva, P M; Mahatha, S K; Ronci, F; Colonna, S; Moras, P; Satta, M; Flammini, R
Abstract: The surface electronic structure of Si(1 1 1)- 7 × 7 has been studied by angle-resolved photo electron spectroscopy. Replicas of the S 1 surface state are found in correspondence with several 7 × 7 unit cells in the reciprocal space. This observation resolves in a direct way the long-standing dichotomy between the structural and electronic properties of the system previously discussed on the basis of the 2 × 2 or 3 × 3 R30° surface models.